Temporal Evolution of Radiated Energy to Seismic Moment Scaling During the Preparatory Phase of the Mw 6.1, 2009 L'Aquila Earthquake (Italy). Issue 8 (18th April 2022) - Picozzi, M.; Spallarossa, D.; Iaccarino, A. G.; Bindi, D.
Abstract: We investigate the preparatory phase of the 2009, Mw 6.1 L'Aquila earthquake in central Italy by analyzing the temporal evolution and spatial distribution of the seismic moment, M0, to radiated energy, ES . Our approach focuses on monitoring the deviations of the scaling between M0 and ES with respect to a model calibrated for the background seismicity. The temporal evolution of these deviations, defined as Energy Index (EI), identifies the onset of the activation phase 1 week before the mainshock. We show that foreshocks are characterized by a progressive increase in slip per unit stress, in agreement with the diffusion of highly pressurized fluids before the L'Aquila earthquake proposed by previous studies. Our results suggest that the largest events occur where energy index (EI) is highest, in agreement with the existing link between energy index (EI) and the mean loading stress. Plain Language Summary: Understanding how the machine generating large earthquakes works is one of the fundamental challenging scientific questions. Pioneering studies have shown that large magnitude earthquakes are sometimes anticipated by foreshocks and slip instabilities. Until now, retrospective analyses of foreshocks during the preparatory phase of large earthquakes have focused mainly on their distribution in space, time and magnitude. In this study, we show that also the dynamic properties of the rupture process associated to foreshocks evolve both in time and space. Our results indicate that the temporal evolution of radiated energy and size of small magnitude earthquakes provide useful information to identify the begin of the final activation phase of the 2009 Mw 6.1 L'Aquila, Italy, earthquake, in agreement with seismicity rate information. Our study suggests that, for the investigated case, foreshocks had dynamic characteristics distinct from those of normal rate (background) seismicity. Thus, it can contribute with new evidence to the open debate whether foreshocks are different phenomena from background seismicity. Key Points: We observe foreshocks dynamic characteristics before the 2009, Mw 6.1 L'Aquila earthquake in central Italy Deviations of radiated energy over seismic moment from a reference model highlight the preparatory phase of the main event Foreshocks are characterized by a progressive increase in slip per unit stress, in agreement with diffusion of highly pressurized fluids